Hydrocarbon Possibilities and Structural Setting in Ad'Daimah Oil Field, Southern Iraq - Khadhaier, Ahmed A.; Ali, Kamal K. (Iraqi Journal of Science, 2024)
Ad'Daimah Field is a structural trap with a proven gas condensate reservoir in limestone. The Yamama Formation is the faulted anticline that makes up the field. Thirteen seismic lines were used for this study, with one well (Da-1). Velocity maps derived from the velocity model were used to construct time and depth maps. Certain stratigraphic features were present in the examined reflector, according to seismic interpretation in the region. In the research area, certain distribution mounds and continuous sand lenses in more than two-dimensional seismic lines were seen. These activity components offer a logical justification for the distribution of hydrocarbons in the study region. The major normal fault of (NW-SE) trending and minor normal faults of (NE-SW) trending, both with a bit of displacement, has been seen in the research region. These fault systems influence the examined reflectors (Yamama, Sulaiy). Time, velocity, and depth maps are created according to the selected reflectors' structural interpretation. The structural interpretation of these reflectors reveals an asymmetrical anticline that extends in an E-W trend, plunges to the southeast with a dip angle of about 5 degrees, and generally dips direction toward NE-SW.